Prognostic Significance of Advanced Age in Patients with T1a Renal Cell Carcinoma Treated by Microwave Ablation: A 16-Year Experience - Qidi Hou MD PhD; Yaxi Wang MD PhD; Dongyun Zhang MS; Yanchun Luo MS; Linan Dong MS; Mengjuan Mu MS; Jie Yu MD PhD; Ping Liang MD PhD (Technology in Cancer Research & Treatment, 2023)
Background Previous studies have failed to investigate the specific effects of advanced age on survival outcomes by considering the Charlson Comorbidity Index (CCI) and age permutation in patients with T1a renal cell carcinoma (T1a RCC) treated by microwave ablation (MWA). Notably, RCC guidelines recommended radiofrequency ablation (RFA) and active surveillance (AS) are both treatment options for elderly T1a RCC, but whether MWA is superior to AS in light of higher heating efficiency and larger ablation zone compared with RFA is not clear. This study aimed to investigate the specific effects of advanced age on survival outcomes of T1a RCC patients stratified by CCI score and indicate better intervention for elderly T1a RCC between MWA and AS. Methods This was a retrospective study. We retrospectively reviewed 237 patients with T1a RCC who had undergone MWA over the last 16 years. Data were analyzed by Cox regression and Landmark analysis. Interaction tests and propensity score matching were used to account for potential biases. We compared the overall survival (OS) and cancer-specific survival (CSS) rates of patients ≥75 years in our study with corresponding figures from 4251 counterparts undergoing AS in published articles. Results Using patients ＜75 years with a CCI ≤2 as a reference, the hazard ratio (HR) and 95% confidence interval (CI) of OS for patients＜75 years with a CCI ≥3, patients ≥75 years with a CCI ≤2, and patients ≥75 years with CCI ≥3, were 2.954 (1.139-7.663), 3.48 (1.487-8.146), and 3.357 (1.162-9.698), respectively. The adverse effect of an age ≥75 years on OS was attenuated in patients with a CCI ≥3. The attenuation lasted for 62.5 months of follow-up ( P  = .017). Notably, advanced age exerted a protective effect on progression-free survival (PFS) in patients with a CCI ≥3, increasing the 8-year PFS from 67.8% to 100% ( P  = .049). Relative to 1-, 3-, 5-, and 8-year survival data for patients aged ≥75 undergoing AS, the OS rates for 5-year follow-up were always better in MWA. However, beyond 5 years, the OS rates dropped to levels that were similar to AS. Conclusions Advanced age exerts adverse effects and significantly protective effects on OS and PFS, respectively, in T1a RCC patients with a CCI ≥ 3. According to our study, elderly patients with T1a RCC underwent radical MWA may yield a better medium-term OS relative to AS.